Evolução microestrutural e propriedades mecânicas decorrentes da solidificação das ligas Al-11%Si-xCu - Donadoni, Bruno Monti Carmelo (Universidade Federal de São Carlos, 2018)
Al-Si-Cu ternary alloys are highly used and recommended to produce joints of aluminum alloys using brazing process. Dissimilar joints between these alloys and stainless steels, carbon steels and low alloy steels can also be fabricated. More specifically, the Al-Si-Cu alloys comprehend the BAlSi-3 brazing class. However, the relationships between the solidification thermal parameters, microstructural parameters and mechanical properties remains undetermined in the literature. In this manuscript the experimental relationships between the mechanical properties and the thermal and microstructural parameters of Al-11%Si-3,0%Cu and Al-11%Si-4,5%Cu ternary alloys will be outlined. Both casting alloys were solidified under transitory heat flow conditions which could be achieved thanks to the unidirectional solidification system. Samples were subjected to a representative range of microstructures due to the broad cooling rate range. Thermodynamics simulations were performed using the Thermo-Calc® software and other analysis have been made to complement the characterization such as X-Ray Diffraction and Scanning Electron Microscopy. At the end, a better comprehension of the formed phases and their chemical composition has been attained. The present work proposes to develop experimental growth relationships for primary, secondary and tertiary dendrite arm spacing, 𝜆1, 𝜆2 and 𝜆3 and eutectic spacing, 𝜆𝑒 impacting the mechanical properties. The experimental results demonstrated that 50% increase in the Cu alloying (from 3.0 to 4.5 wt.%) could be operated to obtain significant variations in the dendritic length-scale of the microstructure across the produced parts. Overall the microstructures is constituted by an α -Al dendritic matrix surrounded by a ternary eutectic consisting of α-Al + Al2Cu + Si. The scale measurements committed to the Al2Cu eutectic phase pointed out that the increase in Cu alloying has a critical role on refining the ternary eutectic.
Microstructural evolution and mechanical properties arising from solidification of AL-11% Si-xCu
Keywords: Ligas Al-Si; Ligas Al-Si-Cu; BAlSi-3; Brasagem; Solidificação; Microestrutura; Propriedades mecânicas; Al-Si Alloys; Al-Si-Cu Alloys; Brazing; Solidification; Microstructure; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS